2014
DOI: 10.1007/s11051-014-2693-7
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced polymer light-emitting diode property using fluorescent conducting polymer-reduced graphene oxide nanocomposite as active emissive layer

Abstract: The present article reports the polymer light-emitting diode property of the nanocomposite comprising poly 9,9-dioctyl fluorene-alt-bithiophene and reduced graphene oxide used as an emissive layer. Two times repetition of Hummers oxidation and hydrazine hydrate reduction method produce reduced graphene oxide (term as rGO2) with more uniform distribution in size and thickness. In addition, this uniquely synthesized rGO2 induces favorable shift in balance of electron and hole recombination zone toward the center… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 57 publications
0
9
0
Order By: Relevance
“…Figure 2 shows multifunction applications of graphene-polymer based nanocomposites. Some conjugated polymer functionalized graphene like polythiophenes or its derivative composites are widely used in photovoltaic devices [30], light-emitting diodes [31,32], transparent conducting electrodes [33], gas barrier membranes [34,35], and biosensors [36][37][38]. Meanwhile, conducting polymers such as polyaniline and polypyrrole functionalized graphene composites show a great potential application in supercapacitors [39,40] and lithium-ion battery electrode [41].…”
Section: Figure 1 Properties Of Graphene-polymer Based Nanocompositesmentioning
confidence: 99%
“…Figure 2 shows multifunction applications of graphene-polymer based nanocomposites. Some conjugated polymer functionalized graphene like polythiophenes or its derivative composites are widely used in photovoltaic devices [30], light-emitting diodes [31,32], transparent conducting electrodes [33], gas barrier membranes [34,35], and biosensors [36][37][38]. Meanwhile, conducting polymers such as polyaniline and polypyrrole functionalized graphene composites show a great potential application in supercapacitors [39,40] and lithium-ion battery electrode [41].…”
Section: Figure 1 Properties Of Graphene-polymer Based Nanocompositesmentioning
confidence: 99%
“…It is pertaining to mention here that the uniform dispersion of nanoparticles into the conducting polymers matrix is an essential requirement to produce synergistic effect in the properties of “hybrid conducting nanocomposites.” Significant enhancements in energy storage properties are thus observed during their device applications. [ 17,18 ] In addition, enhanced mechanical property and improved electrical conductivity are observed in many cases owing to synergetic effect produced by homogeneous dispersion of carbon nanostructured materials (i.e., fullerene, CNT, graphene, etc.) into conducting polymer matrices.…”
Section: Introductionmentioning
confidence: 99%
“…17 But it is not a perfect idea to dope graphene into the emissive layer according to Singh et al's work. 18 This strategy allows electron and hole recombining at the interior of the emitting functional layer more possibly and enhances luminescence and efficiency, but the presence of graphene may cause PL quenching due to electronic interactions. Is there a better way to combine the advantages of graphene and OLED in the emissive layer?…”
Section: ■ Introductionmentioning
confidence: 99%
“…A hole-transport layer doped with graphene, as studied by Posudievsky et al, showed better performance in terms of current density, brightness, and luminous efficiency based on the improved carrier transportation . But it is not a perfect idea to dope graphene into the emissive layer according to Singh et al’s work . This strategy allows electron and hole recombining at the interior of the emitting functional layer more possibly and enhances luminescence and efficiency, but the presence of graphene may cause PL quenching due to electronic interactions.…”
Section: Introductionmentioning
confidence: 99%